Reaching out to youths : a strategic public communications campaign for student advisory centre - Loo, Winnie (2008)
Student Advisory Center’s recent expansion into using extra-curricular activities to help youths at risk had been yielding positive results since its beginning. The program, called Young Achievers’ Club, offers classes such as hip hop dancing, rock climbing and soccer have been, and are still being offered at extremely subsidized rates. Apart from this, SAC has been rapidly expanding into other areas such as Theater Life Skills and the Al-Star program. The campaign was focused on promoting the Young Achiever’s club. Formative research was conducted to survey the responses of subjects and their attitudes. The findings helped us to create an elaborate integrated marketing strategy, that would bring to youths an image of SAC that is fun and hip, while at the same time being a place where they can seek help. The final event was conceptualized to be a dance and music showcase called Hip Hop Battle 2007. The event was to feature hip hop dancers and bands, which were to poses as an example of what youths could achieve through dedications and hard work. Youths received an opportunity to sign up for the classes at the event. More research was conducted during the pre-campaign and post-campaign periods proving that more people had heard about SAC and Hip Hop Battle. Overall, the main part of the report outlines the entire IMC process, a chapter on the event itself, the media coverage and sponsorships received.